Common origin of the gelsolin gene variant in 62 Finnish AGel amyloidosis families. (January 2018) - Mustonen, Tuuli; Schmidt, Eeva-Kaisa; Valori, Miko; Tienari, Pentti; Atula, Sari; Kiuru-Enari, Sari
Abstract Finnish gelsolin amyloidosis (AGel amyloidosis) is an autosomal dominantly inherited systemic disorder with ophthalmologic, neurologic and dermatologic symptoms. Only the gelsolin (GSN ) c.640G>A variant has been found in the Finnish patients thus far. The purpose of this study was to examine whether the Finnish patients have a common ancestor or whether multiple mutation events have occurred at c.640G, which is a known mutational hot spot. A total of 79 Finnish AGel amyloidosis families including 707 patients were first discovered by means of patient interviews, genealogic studies and civil and parish registers. From each family 1-2 index patients were chosen. Blood samples were available from 71 index patients representing 64 families. After quality control, SNP array genotype data were available from 68 patients from 62 nuclear families. All the index patients had the same c.640G>A variant (rs121909715). Genotyping was performed using the Illumina CoreExome SNP array. The homozygosity haplotype method was used to analyse shared haplotypes. Haplotype analysis identified a shared haplotype, common to all studied patients. This shared haplotype included 17 markers and was 361 kb in length (GRCh37 coordinates 9:124003326–124364349) and this level of haplotype sharing was found to occur highly unlikely by chance. ThisGSN haplotype ranked as the largest shared haplotype in the 68 patients in a genome-wide analysis of haplotype block lengths. These results provide strong evidence that although there is a known mutational hot spot atGSN c.640G, all of the studied 62 Finnish AGel amyloidosis families are genetically linked to a common ancestor.